EDUCATIONAL WORK AS A FACTOR PROMOTING DEVELOPMENT OF SOCIAL AND CULTURAL ENVIRONMENT AT THE UNIVERSITY - Marina A. Zamuraeva (Высшее образование в России)
The article presents the main approaches to the organization of pedagogic activities at the university; highlights the basic aspects of the competence approach and its realization at NNGASU. The main focus of the paper is the development of university socio!cultural environment by means of specially organized cultural work and extracurricular activity. The implemented measures at the university prove the effectiveness of the pedagogic activities.